2018
DOI: 10.1097/pec.0000000000000955
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Referrals to an Emergency Department From Urgent Care Centers

Abstract: Many ED referrals directed from urgent care centers in our sample were considered essential, and few were considered serious. Urgent care centers should develop educational and preparedness strategies based on the epidemiology of emergencies that may occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…For pediatric population, abdominal pain is a common complaint in the emergency department (ED) (1). Abdominal pain was reported up to 6.2% of all pediatric emergency admissions (2).…”
Section: Introductionmentioning
confidence: 99%
“…For pediatric population, abdominal pain is a common complaint in the emergency department (ED) (1). Abdominal pain was reported up to 6.2% of all pediatric emergency admissions (2).…”
Section: Introductionmentioning
confidence: 99%
“…This contrasts with previously published data showing high rates of inappropriate pediatric transfer to EDs from general UCCs. In their study of general UCC ED referrals, Olympia et al 9 concluded that 24% (108/455) of pediatric referrals were “nonessential,” defined as not requiring diagnostic/radiologic investigations, procedure sedation, laceration repair, reduction/casting/splinting, subspecialty consultation, or hospitalization. Furthermore, McCarthy et al 8 determined that 27% (29/109) of transferred children in their study did not require ED resource utilization, defined as any ED intervention other than the administration of oral prescription or nonprescription medication or performance of a throat culture or pregnancy test.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Pediatric patients seen in general UCCs have an even higher rate of ED transfer for minor injuries than adults. 8,9 Pediatric UCCs are typically staffed with pediatricians and advanced practice providers (APPs) who have pediatric-specific training. This clinician training may make PUC management and disposition of common, minor pediatric trauma, an area which has not previously been studied, distinct from general UCCs.…”
mentioning
confidence: 99%
“…Representative quotes provide explanation for their lack of experience. procedures education during pediatric residency are all existing barriers to GPeds performing these procedures in their current practice [35,36]. With this in mind, perhaps GPeds do not need to become proficient in all of these procedures during residency training.…”
Section: Discussionmentioning
confidence: 99%